Efficacy of a Benincasa hispida powdered drink in improving metabolic control in patients with type 2 diabetes: A placebo-controlled study - Che Mohd Zin, Che Anis Jauharah; Wan Ishak, Wan Rosli; Abdul Karim Khan, Nurzalina; Wan Mohamed, Wan Mohd Izani (International Journal of Health Sciences, 2024)
Objectives: There is emerging evidence of the benefits of Benincasa hispida in improving metabolic profiles in people with diabetes. This study was conducted to analyze the effect of B. hispida aqueous extract on the metabolic control of patients with type 2 diabetes in Malaysia. Methods: A powdered drink formulated with 2.5 g of B. hispida extract was prepared as a test food. An intervention study was conducted with 50 participants randomly assigned to an intervention or a control group. Anthropometric, biochemical, and clinical variables were assessed at baseline and week 12 after intervention. Paired T-tests were applied to compare the mean differences between the baseline and postintervention for each variable. Results: The intervention group presented a significant reduction in diastolic blood pressure (Δ −7.0 mmHg, 95% confidence interval [CI]: −11.4, −2.5). Mean fasting plasma glucose (Δ −0.8 mmol/L, 95% CI: −1.8, 0.2) showed a greater reduction in the intervention group compared to the control group (Δ −0.4 mmol/L, 95% CI: −1.2, 0.4). Mean lean body mass showed a favorable trend of increment at week 6 (Δ 0.05 kg, 95% CI: −0.40, 0.49) and week 12 (Δ 0.16 kg, 95% CI: −0.33, 0.64) as compared to baseline in the intervention group but not in the control group which manifested decreasing lean body mass. Conclusion: The use of B. hispida extract may potentially improve blood pressure and glycemic control in patients with type 2 diabetes and it may be an attractive candidate for the development of functional food products.